“Spinning In”: The Merger of Canadiana.org with the Canadian Research Knowledge Network / Réseau canadien de documentation pour la recherche - Bengtson, Jonathan; Shepstone, Carol (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
This article explores the background and process that led to the merger of the Canadian Research Knowledge Network / Réseau canadien de documentation pour la recherche and Canadiana.org in 2018. Seizing a moment of opportunity in a rapidly shifting digital research landscape, the two organizations “spun in” to each other in order to leverage their complementary mandates and overlapping memberships. The new merged organization is now better positioned to meet the challenges of collaborative work in research and Canadian heritage content acquisition and access.